Serum Prolactin Level in Yemeni Females with Breast Cancer - Alhaj, Ali A. (University of Science and Technology, Sana'a, 2014)
Background: Breast cancer is one of the most common cancers worldwide. The reproductive hormone prolactin is produced primarily by the pituitary gland and in lesser amounts by several other tissues, including breast tissue. Prolactin plays a central role in breast development, differentiation, and lactation, but experimental data suggest that, in addition to having a role in normal development, prolactin may have pro-carcinogenic effects. Aim: The aim of this research is to study the level of prolactin among Yemeni females with breast cancer. Subjects and Methods: Two groups of subjects were included, 60 patients with histologically confirmed diagnosis of Breast Cancer (group I) and 60 healthy female (group II). For all subjects prolactin (PRL) level was measured by AXSYM System (MEIA) technology. Results and conclusions: Our study showed a significantly increased level of prolactin in breast cancer patients than those of healthy control (P= 0.012), but this elevation remains within normal value (3.4 - 29.12ng/ml). Elevated serum level of PRL (>29.12 ng/ml) was found in 16 of 60 patients (26.7%) and only in 2 subjects (3.33%) in the healthy control group. The results suggest a relation between prolactin level and breast cancer.